ADARs and editing: The role of A-to-I RNA modification in cancer progression. (July 2018) - Fritzell, Kajsa; Xu, Li-Di; Lagergren, Jens; Öhman, Marie
Abstract: Cancer arises when pathways that control cell functions such as proliferation and migration are dysregulated to such an extent that cells start to divide uncontrollably and eventually spread throughout the body, ultimately endangering the survival of an affected individual. It is well established that somatic mutations are important in cancer initiation and progression as well as in creation of tumor diversity. Now also modifications of the transcriptome are emerging as a significant force during the transition from normal cell to malignant tumor. Editing of adenosine (A) to inosine (I) in double-stranded RNA, catalyzed by adenosine deaminases acting on RNA (ADARs), is one dynamic modification that in a combinatorial manner can give rise to a very diverse transcriptome. Since the cell interprets inosine as guanosine (G), editing can result in non-synonymous codon changes in transcripts as well as yield alternative splicing, but also affect targeting and disrupt maturation of microRNA. ADAR editing is essential for survival in mammals but its dysregulation can lead to cancer. ADAR1 is for instance overexpressed in, e.g., lung cancer, liver cancer, esophageal cancer and chronic myoelogenous leukemia, which with few exceptions promotes cancer progression. In contrast, ADAR2 is lowly expressed in e.g. glioblastoma, where the lower levels of ADAR2 editing leads to malignant phenotypes. Altogether, RNA editing by the ADAR enzymes is a powerful regulatory mechanism during tumorigenesis. Depending on the cell type, cancer progression seems to mainly be induced by ADAR1 upregulation or ADAR2 downregulation, although in a few cases ADAR1 is instead downregulated. In this review, we discuss how aberrant editing of specific substrates contributes to malignancy.